Anti-interleukin 6 receptor tocilizumab in refractory uveitis associated with Behçet's disease: multicentre retrospective study. (19th February 2018) - Atienza-Mateo, Belén; Calvo-Río, Vanesa; Beltrán, Emma; Martínez-Costa, Lucía; Valls-Pascual, Elia; Hernández-Garfella, Marisa; Atanes, Antonio; Cordero-Coma, Miguel; Miquel Nolla, Joan; Carrasco-Cubero, Carmen; Loricera, Javier; González-Vela, María C; et al.
Abstract: Objective: To assess the efficacy of tocilizumab (TCZ) in refractory uveitis of Behçet's disease (BD). Methods: Multicentre study of patients with BD-associated uveitis. Patients were refractory to conventional and biologic immunosuppressive drugs. The main outcome measures were intraocular inflammation, macular thickness, visual acuity and corticosteroid-sparing effects. Results: We studied 11 patients (7 men) (20 affected eyes); median age 35 years. Uveitis was bilateral in nine patients. The patterns of ocular involvement were panuveitis ( n = 8, with retinal vasculitis in 4), anterior uveitis ( n = 2) and posterior uveitis ( n = 1). Cystoid macular oedema was present in seven patients. The clinical course was recurrent ( n = 7) or chronic ( n = 4). Before TCZ, patients had received systemic corticosteroids, conventional immunosuppressants and the following biologic agents: adalimumab ( n = 8), infliximab ( n = 4), canakimumab ( n = 1), golimumab ( n = 3), etanercept ( n = 1). TCZ was used as monotherapy or combined with conventional immunosuppressants at 8 mg/kg/i.v./4 weeks ( n = 10) or 162 mg/s.c./week ( n = 1). At TCZ onset the following extraocular manifestations were present: oral and/or genital ulcers ( n = 7), arthritis ( n = 4), folliculitis/pseudofolliculitis ( n = 4), erythema nodosum ( n = 2), livedo reticularis ( n = 1) and neurological involvement ( n = 2). TCZ yielded rapid and maintained improvement in all ocular parameters of the patients, with complete remission in eight of them. However, this was not the case for the extraocular manifestations, since TCZ was only effective in three of them. After a mean (s .d .) follow-up of 9.5 (8.05) months, TCZ was withdrawn in two cases, due to a severe infusion reaction and arthritis impairment, respectively. Conclusion: TCZ could be a therapeutic option in patients with BD and refractory uveitis.